Management of Anxiety Among Village Health Cadre: an Experimental Study - Laila Musalimah; Suci Ratna Estria (Proceedings Series on Health & Medical Sciences, 2022)
Background: Anxiety is experienced by individuals almost every day. Yet, it is unnatural if it happens continuously to be able to disrupt the minds and activities. Lack of information becomes an obstacle in mental health management, especially anxiety. One of the steps to achieving healthy status is the empowerment of mental health cadres through Anxiety Education training.Objective: This study time to determine the effect of anxiety education on the knowledge and skills of cadres in managing anxiety in Suro Village, Kalibagor Sub-District, Banyumas Regency. Method: This study used a pre-experimental design with one group pretest-posttest. The population and samples were 40 respondents selected using the total sampling method. Then, the Wilcoxon test was utilized for the statistical test. Results: This study showed that the majority of respondents are 36-45 years old (35%), and graduated from elementary school level (45%). They worked as housewives (57.5%), and have been being a cadre for 0-10 years (42.5%). The p-value obtained from the Wilcoxon test was 0.000 < 0.05. It meant that there was a significant influence on the level of knowledge and skills of cadres before and after being given anxiety education. Conclusion: Good knowledge would affect the ability and skills of cadres in managing anxiety in their life and in the community.